Physical Activity as a Mediatior in the Relationship Between Oral Health Status and Prevalence of Diabetes in Older Adults - Min-Jun Kim; Taewan Kim; Youngyun Jin; Donghyun Kim (운동과학)
PURPOSE This study examined the mediating effect of physical activity on the association between oral health status and diabetes prevalence in older adults. METHODS We analyzed data from 79,509 participants aged ≥65 years from the 2023 Korea Community Health Survey. Oral health status and periodontal disease information were self-reported, and diabetes diagnosis was confirmed through self-reports. Physical activity levels were assessed based on World Health Organization (WHO) standards. Binary logistic regression was used to estimate the association between oral health, physical activity, and diabetes prevalence. Mediation analysis was conducted using the Hayes Process macro in SPSS to evaluate the mediating role of physical activity. RESULTS Among the 79,509 participants, 19,231 (24.2%) had diabetes, whereas 60,278 (75.8%) did not. Compared with Case 1 of oral health status, the adjusted odds ratios (OR) for Cases 2 and 3 were 1.098 (95% CI, 1.050–1.148; p<.001) and 1.351 (95% CI, 1.297–1.407; p<.001), respectively. Compared with inactivity, the ORs for the insufficiently active and sufficiently active groups were 0.901 (95% CI, 0.845–0.961; p=.001) and 0.772 (95% CI, 0.729–0.817; p<.001), respectively. Mediation analysis showed that physical activity partially mediated the relationship between oral health and diabetes (β=0.004; 95% CI, 0.003-0.005). CONCLUSIONS Poor oral health was associated with diabetes prevalence, and physical activity partially mediated this association. These findings highlight the importance of oral health management and the promotion of physical activity in diabetes prevention and management among older adults.